2020
DOI: 10.1371/journal.pone.0241896
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of re-positive COVID-19 patients in Huangshi, China: A retrospective cohort study

Abstract: A cluster of patients with coronavirus disease 2019 (COVID-19) underwent repeated positive severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA tests after they were discharged from the hospital. We referred to them as re-positive (RP) patients in this study. We aimed to describe the clinical characteristics of these patients in a retrospective cohort study. After being treated for COVID-19, the patients underwent 14 days of quarantine following their discharge from the Huangshi Hospital of Traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Excluded studies and the reason are shown in appendix pp 107–110. Of the 117 eligible studies, there were 66 case reports [ 5 , 16 – 80 ], 42 case series [ 6 , 81 – 121 ], 3 cohort studies [ [122] , [123] , [124] ], 3 cross-sectional studies [ 125 127 ] and 3 case-control studies [ 128 – 130 ]. One hundred studies were from China, 7 from Italy, 3 from Korea, 2 from France, 5 each from Iran, Brunei Darussalam, Switzerland, America and Portugal.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Excluded studies and the reason are shown in appendix pp 107–110. Of the 117 eligible studies, there were 66 case reports [ 5 , 16 – 80 ], 42 case series [ 6 , 81 – 121 ], 3 cohort studies [ [122] , [123] , [124] ], 3 cross-sectional studies [ 125 127 ] and 3 case-control studies [ 128 – 130 ]. One hundred studies were from China, 7 from Italy, 3 from Korea, 2 from France, 5 each from Iran, Brunei Darussalam, Switzerland, America and Portugal.…”
Section: Resultsmentioning
confidence: 99%
“…During the second hospitalization, no RP patients showed any new symptoms, 78·31% showed further improved on chest CT scan compared with the first discharge. None of the close contacts developed COVID-19 Peng et al [117] China Case series 9 5 7·2 ± 4·8 14/38 positive positive positive Family cluster infection, higher WBC count, and longer plasma prothrombin time (PT) are the early risk factors for RP in recovered COVID‐19 children Landi et al [115] Italy Case series 10 12 56·4 ± 15·7 22/131 14 d positive Persistent sore throat (prevalence ratio=6·50, 95% CI 1·38, 30·6) and symptoms of rhinitis (prevalence ratio=3·72, 95% CI 1·10, 12·5) were risk factors for retesting positive for SARS-CoV-2 Zhou et al [121] China Case series 16 7 51·0(42–58) 23/368 14 d positive Using multivariate Cox regression analysis, risk factors associated with RP included a higher ratio of lymphocyte/white blood cell on admission, lower peak temperature during hospitalization, and the presence of comorbidities, particularly hypertension or chronic respiratory system diseases. Antivirus treatment with arbidol was associated with a lower likelihood of RP Huang et al [114] China Case series 41 28 69/417 14 d positive …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations